The influence of psychological capital on career satisfaction in nurses at MADINA Hospital Bukittinggi with work engagement as a mediating variable - Irenia, Audrey Nada; Syahrizal, Syahrizal (Universitas Negeri Padang, 2025)
Primary objective of this research is to evaluate (1) the impact of psychological capital on career satisfaction among nurses at MADINA Hospital. 2) The impact of psychological capital on the level of work engagement among nurses at MADINA Hospital. (3) The impact of work engagement on the perception of career satisfaction among nurses at MADINA Hospital. (4)The mediating variable of work engagement in the relationship between psychological capital and career satisfaction among nurses at MADINA Hospital. The data analysis method employed in this study was SEM analysis, which was conducted using the Smart PLS 4 application. The total sampling technique was employed to select 73 respondents for the study, which corresponds to quantitative descriptive research.. The findings of the research are as follows: (1) nurses at MADINA Hospital experience a substantial impact of psychological capital on their career satisfaction. (2) The work engagement of nurses at MADINA Hospital is significantly influenced by psychological capital. (3) There is no substantial correlation between career satisfaction and work engagement among nurses at MADINA Hospital. (4) Work engagement serves as a mediating variable, and psychological capital does not have a notable impact on career satisfaction among nurses at MADINA Hospital.